Accessory spleen. A diagnostic challenge. Case Study. - Celi Simbaña, Stalin Santiago; Andrade Mora, Diego Sebastián; Mendoza Benalcázar, Jessica Estefania (Radiography Open, 2022)
Introduction: Accessory spleen, also called supernumerary spleen, is a generally benign and asymptomatic condition, characterized by the location of splenic tissue outside the spleen. Its prevalence has been reported between 10% to 30% of the population. Materials and Methods: Patient evaluated for recurrent urinary tract infection in which a computed tomography urography without contrast was requested, incidentally finding an accessory spleen. Results: Clinical case report and diagnostic imaging challenge. Conclusions: The accessory spleen is a condition of congenital origin, relatively frequent for which it should be considered in the spectrum of the differential diagnosis of acute abdomen and intra-abdominal masses since its timely diagnosis can avoid unnecessary surgeries.